Congenital Midureteric Stricture: Challenges in Diagnosis and Management - Raashid Hamid; Nisar A. Bhat; Kumar Abdul Rashid (Case Reports in Urology)
Background. Congenital midureteric stricture (MUS) is a rare malformation. We report our experience with five cases seen over a period of 4 years from 2010 to 2014. Materials and Methods. The study was based on the retrospective analysis of five patients diagnosed as having MUS. Diagnosis was suspected after fetal ultrasonography (USG) in one patient and magnetic resonance urography (MRU) in four patients. Retrograde pyelography (RGP) was performed on three patients. The final diagnosis was confirmed during surgical exploration in all the patients. Results. MRU was found to be a good investigation method. It showed the site of obstruction in the ureter in all instances. Intravenous urography detected proximal ureteric dilatation present in two of the patients. RGP delineates the level of stricture and the course of ureter, as shown in our cases. All patients had significant obstruction on the affected side. Four patients underwent ureteroureterostomy, all of whom had satisfactory results. In one patient, ureteric reimplantation was carried out due to distal small ureteric caliber. Conclusion. This rare entity is often misdiagnosed initially as pelviureteric junction obstruction. MRU is an excellent option for the anatomical location and functional assessment of the involved system. At the time of surgical correction of a ureteral obstruction, RGP is a useful adjunct for delineating the stricture level and morphology.